# SOLUTION: Solve. If problem has no solution; write no solution. 1 = 3 over y+2 + 1 over y-2 Here is what I have: (y+2)(y-2) = 3(y-2)+ y + 2 y^2 + 2y - 2y - 4 = 3y - 6

Algebra ->  Algebra  -> Numeric Fractions Calculators, Lesson and Practice -> SOLUTION: Solve. If problem has no solution; write no solution. 1 = 3 over y+2 + 1 over y-2 Here is what I have: (y+2)(y-2) = 3(y-2)+ y + 2 y^2 + 2y - 2y - 4 = 3y - 6       Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Numeric Fractions Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on Numeric Fractions Question 69181This question is from textbook Algebra Structure and Method : Solve. If problem has no solution; write no solution. 1 = 3 over y+2 + 1 over y-2 Here is what I have: (y+2)(y-2) = 3(y-2)+ y + 2 y^2 + 2y - 2y - 4 = 3y - 6 + y + 2 y^2 - 4 = 4y - 4 and that is as far as I got, I am lost This question is from textbook Algebra Structure and Method Answer by Earlsdon(6287)   (Show Source): You can put this solution on YOUR website!You did fine as far as you went so let's continue from where you left off: Add 4 to both sides of the equation. Subtract 4y from both sides. Factor a y on the left side. Apply the zero product principle. and/or The solutions are: